Small-diameter bacterial cellulose-based vascular grafts for coronary artery bypass grafting in a pig model - Fusco, Deborah; Meissner, Florian; Podesser, Bruno K.; Marsano, Anna; Grapow, Martin; Eckstein, Friedrich; Winkler, Bernhard (Frontiers in Cardiovascular Medicine, 2022)
Surgical revascularization is the gold standard in most cases of complex coronary artery disease. For coronary artery bypass grafting, autologous grafts are state-of-the-art due to their long-term patency. A non-negligible amount of patients lack suitable bypass material as a result of concomitant diseases or previous interventions. As a promising alternative, tissue-engineered vascular grafts made of biomaterials such as bacterial cellulose (BC) are gaining more and more attention. However, the production of small-diameter grafts (inner diameter < 6 mm) of application-oriented length (> 5 cm) and their in vivo long-term patency remain challenging. In this study, grafts of 20 cm in length with an inner diameter of 3 mm were generated in a custom-made bioreactor. To potentially improve graft compliance and, therefore in vivo patency, BC was combined with an embedded cobalt–chromium mesh. The grafts were designed for in vivo endothelialization and specific surgical properties and implanted as an aortocoronary bypass in a left anterior descending occluded pig model (n = 8). Coronary angiography showed complete patency postoperatively at 4 weeks. Following 4 weeks in vivo, the grafts were explanted revealing a three-layered wall structure. Grafts were colonized by smooth muscle cells and a luminal layer of endothelial cells with early formation of vasa privata indicating functional remodeling. These encouraging findings in a large animal model reveal the great potential of small-diameter BC grafts for coronary and peripheral bypass grafting.